2017
DOI: 10.5301/jsrd.5000256
|View full text |Cite
|
Sign up to set email alerts
|

What have multicentre registries across the world taught us about the disease features of systemic sclerosis?

Abstract: The aim of this study is to compare the clinical features, mortality and causes of death of systemic sclerosis (SSc) patients in four large multicentre registries. Methods: Patients seen at least once in the Australian Scleroderma Cohort Study (ASCS) (n = 1714), the Canadian Scleroderma Research Group (CSRG) (n = 1628), the European League Against Rheumatism Scleroderma Trials and Research (EUSTAR) Network (n = 13,996) and the Systemic Sclerosis Cohort in Singapore (SCORE) (n = 500) before August 2016 were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…SSc has one of the highest morbidities and case-specific mortalities amongst the connective tissue diseases [2,3]. Overall, general health (as measured by the SF-36 and EQ-5D questionnaires), as well as quality of life and functional abilities (as measured by the Health Assessment Questionnaire Disability Index, HAQ-DI) are significantly reduced in SSc [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…SSc has one of the highest morbidities and case-specific mortalities amongst the connective tissue diseases [2,3]. Overall, general health (as measured by the SF-36 and EQ-5D questionnaires), as well as quality of life and functional abilities (as measured by the Health Assessment Questionnaire Disability Index, HAQ-DI) are significantly reduced in SSc [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the findings from our study may be generalized to patients of Asian descent. Previous studies demonstrated no significant differences in initial or peak mRSS between SSc patients of Asian descent and their European counterparts …”
Section: Discussionmentioning
confidence: 87%
“…SSc is more frequent in the female gender and in the Caucasian race, and usually starts at an adult age. 3 Its prevalence seems to be higher in North America and Australia compared to Europe and Japan. 4,5 It is important to consider that juvenile-onset SSc, despite being a rare disease, can present a distinct clinical and immunological profile, with a distinct outcome, when compared with adult-onset SSc patients.…”
Section: Introductionmentioning
confidence: 99%
“…SSc is more frequent in the female gender and in the Caucasian race, and usually starts at an adult age. 3 Its prevalence seems to be higher in North America and Australia compared to Europe and Japan. 4,5…”
Section: Introductionmentioning
confidence: 99%